2020
DOI: 10.1371/journal.pone.0228717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conservation farming and biochar addition on soil organic carbon quality, nitrogen mineralization, and crop productivity in a light textured Acrisol in the sub-humid tropics

Abstract: Conservation farming (CF), involving basin tillage, residue retention and crop rotation, combined with biochar may help to mitigate negative impacts of conventional agriculture. In this study, the effects of CF on the amount and quality of soil organic matter (SOM) and potential nitrogen (N) mineralization were investigated in a maize-soya-maize rotation in an Acrisol in Zambia. A large field was run under CF for 7 years and in the subsequent three growing seasons (2015-2018), four management practices were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 60 publications
1
13
0
1
Order By: Relevance
“…Mulvaney et al (2010) found that the N mineralization rate of soil was increased with the application of crop residue combined with conventional or conservation tillage condition. There was a negative correlation between soil chemical characteristics and soil N mineralization rates (Munera-Echeverri et al, 2020). The results from previous studies indicated that soil organic matter (SOM) quantity and quality can be determined by soil aerobic and anaerobic N mineralization rates (Kader et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Mulvaney et al (2010) found that the N mineralization rate of soil was increased with the application of crop residue combined with conventional or conservation tillage condition. There was a negative correlation between soil chemical characteristics and soil N mineralization rates (Munera-Echeverri et al, 2020). The results from previous studies indicated that soil organic matter (SOM) quantity and quality can be determined by soil aerobic and anaerobic N mineralization rates (Kader et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Different crops vary in the quantity, quality, and frequency of OM inputs. In this way, within the same system, different crop rotations could impact SOC [26,37,79,[124][125][126]. The decomposition rate of CR (thus, the remaining SOC in the soil) is a function of many factors, including the type of CR [127][128][129][130][131].…”
Section: Effect Of Crop Residue and Crop Rotation On Socmentioning
confidence: 99%
“…In addition, potassium can improve the quality of plants, one of which is to increase the content of starch, oil, or other secondary metabolite compounds. Besides the two elements mentioned above, organic matter such as plant residues can increase N mineralization in the soil [21]- [24]. Changes in N in the soil will increase yields by 26 -41% [25] and is one of the main plant nutrients involved in chlorophyll synthesis, and affects stomata conductance and photosynthetic.…”
Section: Introductionmentioning
confidence: 99%